Clinical and microbiological evaluation of the use of toothpaste containing 1% chlorhexidine and the influence of motivation on oral hygiene in patients with motor deficiency - De Andrade Meyer, Augusto Cesar [UNESP]; De Mello Tera, Tábata [UNESP]; Da Rocha, João Carlos [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (Wiley, 2010)
Patients with motor deficiency have variable difficulties with mechanical plaque control, and as a consequence, the incidence of dental caries and periodontal disease can be higher in these patients. The objective of this study was to evaluate the clinical and microbiological efficacy of a toothpaste containing 1% chlorhexidine, which was used by patients with motor deficiency for 14 days. The reduction in plaque and gingival index and the impact on salivary microorganisms was evaluated. We conclude that the motivation of caregivers to carry out oral hygiene for patients with mental and motor deficiency is of great importance and is effective in reducing the formation of plaque as long as it is continuously reinforced. The use of chlorhexidine- containing toothpaste significantly reduced the plaque index and microorganism count between days 0 and 14. A reduction was also observed in the group that used a dentifrice without the chlorhexidine, but this difference was not significant. © 2010 Special Care Dentistry Association and Wiley Periodicals, Inc.
Keywords: Chlorhexidine; Motor deficiency; Oral hygiene; Toothpaste; chlorhexidine; toothpaste; topical antiinfective agent; adolescent; bacterial count; caregiver; cerebral palsy; child; clinical trial; comparative study; controlled clinical trial; controlled study; developmental disorder; double blind procedure; feeding behavior; female; follow up; gingivitis; human; instrumentation; male; mental disease; methodology; microbiology; motivation; mouth hygiene; pathophysiology; periodontics; randomized controlled trial; saliva; tooth brushing; tooth plaque; Adolescent; Anti-Infective Agents, Local; Caregivers; Cerebral Palsy; Child; Colony Count, Microbial; Dental Plaque; Dental Plaque Index; Developmental Disabilities; Double-Blind Method; Female; Follow-Up Studies; Food Habits; Gingivitis; Humans; Male; Mental Disorders; Motivation; Oral Hygiene; Periodontal Index; Saliva; Toothbrushing; Toothpastes